1994
DOI: 10.1063/1.355651
|View full text |Cite
|
Sign up to set email alerts
|

The initial phases of epitaxy of fcc Fe/Cu(100): Supersurface and subsurface island formation

Abstract: Nanometer transverse resolved real space observations of the initial phases of room-temperature heteroepitaxy of fcc Fe/Cu(100) indicate that vertical atomic site exchange occurs locally. The formation of two-dimensional supersurface and subsurface islands has been characterized by secondary and Auger electron imaging. The persistence of vertical site exchange during the deposition of the first two monolayers is not inconsistent with the lack of observed ferromagnetism for the room-temperature grown fcc Fe/Cu(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Second, deposition of Fe at RT does not follow the layer growth mode, but probably corresponds initially to island growth with high nucleation densities, as has been found recently for Fe/Au(111) (Stroscio et al 1992) and Fe/Cu(100) (Healy et al 1994). However, even at RT, this is in competition with subsurface exchange of Fe with Ag.…”
Section: Application To Fe/ag/fe(110) Heterostructuresmentioning
confidence: 70%
See 1 more Smart Citation
“…Second, deposition of Fe at RT does not follow the layer growth mode, but probably corresponds initially to island growth with high nucleation densities, as has been found recently for Fe/Au(111) (Stroscio et al 1992) and Fe/Cu(100) (Healy et al 1994). However, even at RT, this is in competition with subsurface exchange of Fe with Ag.…”
Section: Application To Fe/ag/fe(110) Heterostructuresmentioning
confidence: 70%
“…However, even at RT, this is in competition with subsurface exchange of Fe with Ag. From the data shown in figure 6, it seems likely that this is most intense up to 2 ML Fe, after which a more or less pure Fe layer is deposited; microscopic Auger studies of Fe/Cu(100) suggested a similar result (Healy et al 1994). Annealing a 9 ML deposit (250 • C for 5 min) results in an increase in the Ag Auger signal, probably caused by diffusion between, and over the Fe crystallites.…”
Section: Application To Fe/ag/fe(110) Heterostructuresmentioning
confidence: 92%
“…For f.c.c (f.c.t) Fe, a non-magnetic, high and low spin, or an anti-ferromagnetic phase can be stable depending upon the lattice constant [51]. Our Fe/Cu(100) studies, both on and off MIDAS, lasted nearly 3 years, resulting in the theses of Kevin Heim [52], Zhijun Yang [53] and many papers [54][55][56][57][58][59], with the participation of Masters student Sean Healy. A set of hysteresis loops taken with the SMOKE system is shown in Figure 9.…”
Section: Applications To Magnetic Materialsmentioning
confidence: 99%